Avaliação epidemiológica de doentes mentais em casas de acolhimento de idosos na região sudoeste mineiro-Brasil - Giubilei, Maurício (2006)
Aims The authors tried to identify de-hospitalized mentally ill patients living in shelters or homes and then quantify and stratify them as to their destinations residence and behavior specially towards other residents in Elderly Homes The de-hospitalizations took place by the end of the 80s with changes to the Mental Health policy the creation of Paulo Delgado law and the consequent deactivation of psychiatric beds in Brazil mainly in Minas Gerais state Methods Two questionnaires were made one for the Elderly Homes and the other for their residents The survey only began after a Term of Consent was signed authorizing the participation in this study The first questionnaire consisted of questions regarding care homes themselves their managers main religion budget source number of employees and their specific duties Main types of covenants public or private endowments for specific and complementary assistance as well as the number of beds for elderly and mentally ill residents were also evaluated The Ministry of Health regulations regarding mentally ill patients were unknown to their managers As to the boards of directors they found it acceptable to have both mentally ill and elderly persons in the same environment However they were careful to explain the discomfort of this sociability Psychiatric support or specific hospitals were acknowledged The questionnaire consisted of residents data sociofamiliar factors psychiatric and psychological diagnostics medication and dosages Those residents coming from hospitals number of specialized psychiatric confinements and their behavior adjustments were also considered 520 residents in 11 homes located in 10 cities in the southwest region of Minas Gerais were evaluated Results Gender distribution was the same Average age was 22 to 100 years old (65,60 ± 14,39) Ages between 51 and 70 years old corresponded to 48,65% while in 82.49% of residents the ages were between 51 and 90 years Caucasian was 70.60% Regarding the laboring capacity 67.90% was between none and little Of all residents evaluated 72.90% had never had a psychiatric hospitalization and 10.40% had been hospitalized more than five times The results show that 20.00% of all residents suffer from dementia 19.80% were chronic psychotics and 13.30% schizophrenics 21.70% were mentally ills and 12.70% was the percentage of healthy residents The remaining residents presented other neuropsychiatric diagnostics 3,70% (19) were de-hospitalized from Psychiatric Hospital In general 15.30% had inadequate behaviors which interferes in their daily life and 64.40% make daily use of psychotropic medication against 35.60% who uses with non-psychotropic drugs or only and nothing at all Of the psychotropic medications used haloperidol is the main in 35.20% followed by diazepam 34.00% Biperideno 23.00% followed by Phenobarbital 21.50% and amitriptyline 14.90% Conclusion The study concluded that the number of psychiatric patients de-hospitalized and transferred to Elderly Homes was little in the evaluated area However a significant number of patients with chronic characteristics who alternated between Elderly Homes and Psychiatric Hospitals were identified Most of the Elderly Homes avoided residents with some sort of mental disorder especially schizophrenic ones Other chronic psychiatric patients with light symptoms and lack of monetary and family support were accepted in as a matter of philanthropy and humanity